Understanding the outcome and management of children aged 2–59 months with chest indrawing pneumonia: a study protocol for an observational study in Ethiopia, India, Nigeria, Pakistan, Uganda and Zambia - Cipam Study Group, Chest Indrawing Pneumonia Management (BMJ Publishing Group LTD, 2024)
Abstract IntroductionChildhood pneumonia is a leading cause of morbidity and mortality among children aged 2–59 months, particularly in low-income and middle-income countries (LMICs), where healthcare providers face significant challenges in diagnosing and treating childhood pneumonia. Many LMICs have taken steps to address this issue by revising their national policies and aligning them with WHO’s revised guidelines for pneumonia management. These revised guidelines aim to facilitate the outpatient management of children aged 2–59 months chest indrawing pneumonia. Despite these efforts, there is limited empirical evidence regarding the management and outcomes of these children in primary-level healthcare settings. This study aims to assess the survival status of children aged 2–59 months with chest indrawing pneumonia presenting at primary healthcare facilities.Methods and analysisA prospective, observational cohort study will be conducted in Ethiopia, Nigeria, Uganda, Zambia, India and Pakistan on children aged 2–59 months presenting at selected primary-level healthcare facilities with chest indrawing pneumonia. Eligible participants will be enrolled and managed by facility healthcare providers who are trained in Integrated Management of Childhood Illness and will be followed up on day 15 to record the treatment-related information and vital status, including conducting verbal autopsies in case of child death. The sample size for each site will be 310. The analysis will involve exploring site-specific trends before conducting a pooled analysis of de-identified data from all sites. The first data collection started at the Ethiopian site in September 2022, followed by other sites. The data collection will continue until June 2025.Ethics and disseminationThe study protocol, enrolment forms and consent forms will undergo ethical review by the Institutional Review Boards of the University of Gondar, Gondar, Ethiopia; the INCLEN Trust International Independent Ethics Committee, New Delhi, India; Ethical Review Committee of the University of Ibadan, Ethical Review Committees of Lagos State and Ethical Review Committee of University College London, UK; Institutional Review Board, International Research Force, Islamabad, Pakistan; Institutional Review Board, People’s Primary Healthcare Initiative-Sindh, Karachi and National Bioethics Committee, Islamabad, Pakistan; Makerere University School of Biomedical Sciences Research Ethical Committee, Kampala, Uganda; University of Zambia Biomedical Research Ethics committee, Lusaka, Zambia and Ethical Review Committee of WHO, Geneva, Switzerland. Ethical procedures include WHO and local review board evaluations, parental consent in the local/national language, permits enrolment, follow-up, and, if required, clinical video recording for children with chest indrawing pneumonia, ensuring their eligibility. Adherence to local regulations encompasses precollection ethical approvals, risk management strategies and secure, de-identified data storage. Findings will be disseminated through seminars, publications and meetings, engaging diverse stakeholders to foster collaborations.Trial registration numberISRCTN12687253. Publicly Available Content Database